Inflammasome adaptor protein ASC is a mechanistic checkpoint in IL-1β maturation - Giti Saha; Pratibha Anchi; Richard Wang; Alyssa Biondo; Sadie Meyer; Vinata Kondragunta; Larry L. Luchsinger; Ismail Syed; Humayun Sharif; Hao Wu; Venkat Giri Magupalli (Proceedings of the National Academy of Sciences, 2026)
Inflammasome activation triggers caspase-1-dependent maturation of pro-interleukin-1β (pro-IL-1β) in an apoptosis-associated speck-like protein containing a CARD (ASC)-dependent manner, yet the mechanism by which pro-IL-1β is physically recruited to the ASC signaling platform has remained undefined. Here, we identify the ASC linker domain (ASC LD ) as a noncanonical protein-interaction interface, that can directly recruits pro-IL-1β onto the ASC speck. Using a live-cell NanoBRET assay, confocal imaging, and pulldown analysis, we show that ASC directly engages pro-IL-1β and that this interaction requires a discrete set of charged residues in the IL-1β mature domain region, forming an ASC-docking surface. Mutagenesis guided by the IL-1β structure confirmed that this interaction is essential for caspase-1-dependent IL-1β maturation but dispensable for pyroptosis. Domain mapping revealed that ASC LD , rather than its N-terminal Pyrin domain (PYD) or C-terminal caspase recruitment domain (CARD), mediates pro-IL-1β recruitment. Using an in-house custom antibody against ASC LD , we show that this region remains exposed within endogenous ASC specks in macrophages. Mutational disruption of ASC LD selectively impaired IL-1β processing in THP-1 cells Mutations disruption data was obtained from THP-1 cells without affecting ASC speck formation or pyroptosis. A cell-penetrating peptide derived from ASC LD selectively blocked pro-IL-1β docking while preserving speck assembly. In 2 mouse models of peritonitis, the blocking peptide uncoupled cytokine maturation from pyroptosis and significantly reduced IL-1β-driven inflammation. Thus, our findings uncover ASC LD as a critical docking interface that positions pro-IL-1β for efficient caspase-1 processing, which adds a mechanistic checkpoint within inflammasomes to license cytokine maturation independently of pyroptotic death. We propose that ASC LD may be a therapeutically tractable node for selective modulation of IL-1β-driven inflammasomopathies.